2018
DOI: 10.1101/304634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seed predation increases from the Arctic to the Equator and from high to low elevations

Abstract: Species interactions have long been predicted to increase in intensity towards the tropics and low elevations, due to gradients in climate, productivity, or biodiversity. Despite their importance for understanding global ecological and evolutionary processes, plant-animal interaction gradients are particularly difficult to test systematically across large geographic gradients, and evidence from smaller, disparate studies is inconclusive. By systematically measuring post-dispersal seed predation using 6980 stan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
39
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 59 publications
8
39
0
Order By: Relevance
“…Warmer temperatures can also increase parasite overwintering success (Burdon & Elmqvist 1996; Pfender & Vollmer 1999) or allow parasites to produce more generations during a longer growing season (Garrett et al 2006). These results corroborate past studies suggesting that environmental gradients can directly alter the strength of biotic interactions (Schemske et al 2009; Pellissier et al 2014; Descombes et al 2017; Roslin et al 2017; Hargreaves et al 2019), including host-parasite interactions (Nunn et al 2005; Abbate & Antonovics 2014; LaManna et al 2017; Allen et al 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Warmer temperatures can also increase parasite overwintering success (Burdon & Elmqvist 1996; Pfender & Vollmer 1999) or allow parasites to produce more generations during a longer growing season (Garrett et al 2006). These results corroborate past studies suggesting that environmental gradients can directly alter the strength of biotic interactions (Schemske et al 2009; Pellissier et al 2014; Descombes et al 2017; Roslin et al 2017; Hargreaves et al 2019), including host-parasite interactions (Nunn et al 2005; Abbate & Antonovics 2014; LaManna et al 2017; Allen et al 2020).…”
Section: Discussionsupporting
confidence: 91%
“…The LBIH, which was originally developed for among‐biome comparisons (Dobzhansky, 1950; Schemske et al., 2009), has been supported by several macroecological studies of predation (Hargreaves et al., 2019; Jeanne, 1979; Roslin et al., 2017). A few studies found a poleward decrease in predation rates within the temperate biome (DeGregorio et al., 2016; Thompson & Ribic, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…(DeGregorio et al., 2016; Roslin et al., 2017; Thompson & Ribic, 2012; Zvereva et al., 2019). These latitudinal changes in predation are frequently associated with changes in the abundance of invertebrate predators (Hargreaves et al., 2019; Roslin et al., 2017). We suggest that the decline in ant predation in our latitudinal gradient was also driven mainly by a decline in ant abundance: analysis of the soil macrofauna in the same gradient showed a substantial poleward decrease in the density of predatory ants (M. Kozlov, unpubl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2016; Moles & Ollerton 2016; Roslin et al . 2017; Baskett & Schemske 2018; Hargreaves et al . 2019; Freeman et al .…”
Section: Introductionmentioning
confidence: 99%